Semifluorinated PMMA Block Copolymers: Synthesis, Nanostructure, and Thin Film Properties - Pospiech, Doris; Jehnichen, Dieter; Eckstein, Kathrin; Scheibe, Philipp; Komber, Hartmut; Sahre, Karin; Janke, Andreas; Reuter, Uta; Haeussler, Liane; Schellkopf, Leonard; Friedel, Peter; Voit, Brigitte (Macromolecular Chemistry and Physics, 2017)
Diblock copolymers (BCP) with poly(methyl methacrylate) and poly(1H,1H,2H,2H-perfluorodecyl methacrylate) (PsfMA) blocks prepared by anionic polymerization in tetrahydrofuran at −78 °C and atom transfer radical polymerization (ATRP) at 60 °C, respectively, with stepwise varied composition over a wide range in the phase diagram are compared with respect to synthesis limits, phase separation behavior in bulk, and properties of thin films. Both methods yield BCPs with low dispersity (1.1–1.2) at molar masses below 100 kg mol−1. Higher semifluorinated contents can be achieved by ATRP in 1,3-bis(trifluoromethyl)benzene which ensured solubility of PsfMA. BCPs obtained by anionic polymerization show a more distinct phase separation, that is, more regular nanostructures. Additionally, self-organization of the semifluorinated side chains occurs generating smectic layers which alters in turn the BCP morphology especially in thin films as compared to non-semifluorinated BCP. All BCPs show amphiphilic behavior and form micelles in organic solvents which can be used to deposit nanoparticles. (Figure presented.).
CRIS-Team Scopus Importer:2022-04-14
Keywords: anionic polymerization; ATRP; block copolymers; nanophase separation